Pengaruh Pendidikan, Pengalaman Kerja dan Prestasi Kerja Terhadap Pengembangan Karir Pegawai pada Unit Penyelenggara Bandar Udara (UPBU) Djalaluddin Gorontalo - Meri Modjo; Yakup; Sasmita R. Setiawan (Mabsya: Jurnal Manajemen Bisnis Syariah, 2022)
Career development in human resource management is very important because career development will produce human resources who are professional and have high competence in an organization. Employee career development is influenced by several factors including education, work experience, and work achievement. The aim of this research is to analyze the effect of education, work experience, and work achievement on career development at UPBU Djalaluddin Gorontalo either partially or simultaneously. The population in this research amounted to 90 respondents. Sampling used the census method so that the entire population was sampled. Methods of data analysis using multiple regression analysis. The results showed that partially and simultaneously, education, work experience, and work achievement had a positive and significant impact on career development at UPBU Djalaluddin Gorontalo. Keywords: Education, Work Experience, Work Achievement, Career Development